Don't slap the fish: The relationship between dietary omega-3 intake and physical aggression is mediated by motor inhibition in response to distressed faces. (1st February 2021) - Fido, Dean; Heym, Nadja; Bloxsom, Claire A.J.; Hunter, Kirsty A.; Gregson, Michael; Sumich, Alexander
Abstract: The innate violence inhibition mechanism (VIM) purportedly regulates maladaptive aggressive behavior through motor inhibition, in response to expressions of distress, and is implicated in psychopathy-related aggression. Deficiency in eicosapentaenoic acid (EPA; an omega-3 fatty acid) is implicated in aggression and callous-unemotional (CU) traits, however, its relationship to the VIM remains unknown. Two studies tested relationships between EPA intake, personality (aggression, CU traits), and electrophysiological indices of the VIM. In study one (N = 98), participants completed omega-3 intake (FFQ), CU traits (ICU), and aggression (BPAQ) measures. Physical aggression correlated positively with callousness and negatively with EPA intake. CU traits were unrelated to EPA. In study two (N = 47), participants completed the same measures and an electroencephalography assessment of VIM. Stop-P300 amplitude (motor inhibition success) in response to facial expressions of distress mediated the relationship between EPA intake and physical aggression. This is the first demonstration of an association between EPA intake and electroencephalographic indices of the VIM. Findings support a role of EPA in regulating aggression through networks involved in distress-cued executive control over behavior; and provide supporting data to direct future trial designs for nutritional supplementation in non-clinical, clinical and forensic arenas. Highlights: Eicosapentaenoic acid (EPA) is associated with reduced physical aggression. In a general population, self-reported EPA intake is not associated with CU traits. Stop-P300 amplitude to distressed faces mediates the link between EPA & aggression. EPA plays a role in a motor inhibition stage of the violence inhibition mechanism.